Hubungan Antara Personal Hygiene Dan Status Anemia Dengan Kejadian Infestasi Pediculus Humanus Capitis Pada Santri Kelas 1 Madrasah Tsanawiyah Di Pondok Pesantren “ Assaasunnajah “ Ateuk Lung Ie Kecamatan Ingin Jaya Provinsi Aceh Besar - Dwi Haryatmi (Universitas Muhammadiyah Surabaya, 2024)
Pediculosis humanus capitis is a blood-sucking parasite that spends its entire life cycle on the human scalp. Poor personal hygiene can affect pediculosis capitis infection. In school children, the chronic infestation of pediculosis capitis causes anemia and makes children lethargic and sleepy. The aim of the study was to determine the relationship between personal hygiene and anemia status with the incidence of pediculus humanus capitis in first grade students at madrasah tsanawiyah at the